Microtubule-organizing center polarity and the immunological synapse: protein kinase C and beyond - Huse, Morgan (Frontiers in Immunology, 2012)
Cytoskeletal polarization is crucial for many aspects of immune function, ranging from neutrophil migration to the sampling of gut flora by intestinal dendritic cells. It also plays a key role during lymphocyte cell–cell interactions, the most conspicuous of which is perhaps the immunological synapse (IS) formed between a T cell and an antigen-presenting cell (APC). IS formation is associated with the reorientation of the T cell’s microtubule-organizing center (MTOC) to a position just beneath the cell–cell interface. This cytoskeletal remodeling event aligns secretory organelles inside the T cell with the IS, enabling the directional release of cytokines and cytolytic factors toward the APC. MTOC polarization is therefore crucial for maintaining the specificity of a T cell’s secretory and cytotoxic responses. It has been known for some time that T cell receptor (TCR) stimulation activates the MTOC polarization response. It has been difficult, however, to identify the machinery that couples early TCR signaling to cytoskeletal remodeling. Over the past few years, considerable progress has been made in this area. This review will present an overview of recent advances, touching on both the mechanisms that drive MTOC polarization and the effector responses that require it. Particular attention will be paid to both novel and atypical members of the protein kinase C family, which are now known to play important roles in both the establishment and the maintenance of the polarized state.